Ubud: Benteng Terbuka - Graeme MacRae (Jurnal Kajian Bali (Journal of Bali Studies), 2014)
AbstractThis article discusses evolution and present problems of Ubud as a tourist town in the context of Bali tourismdevelopment. Ubud has always provided an alternativevision of what tourism in Bali could be. The metaphor of an Open Fortress provides a useful lens for looking at Ubudover the past century. “Tourism” is in Ubud has always been closely linked to an expatriate community and other international economic activities. Tourism is not a oneway process – it is always a dialectical process between local communities and visitors (as Michel Picard told uslong ago). This process is always changing and in Ubud ithas now entered a new phase – involving a tourism/expatnexus that is quite disconnected from local community andculture.